Strengthening the Internalization of Pancasila Values in the Millennial Generation Through Character Education in Indramayu Regency - Ali Miftakhu Rosyad; Taufik Hidayat; Nurchamidah Nurchamidah; Muhamad Baedowi; Muhammad Hamsah (Jurnal Pengabdian Masyarakat Sultan Indonesia, 2026)
The degradation of Pancasila values among the millennial generation challenges the resilience of national ideology in the digital era. This community service program aimed to strengthen the internalization of Pancasila values through a local wisdom-based participatory action learning approach for millennials in Indramayu Regency involving 120 participants from university students, Karang Taruna members, and community activists aged 18–35 years. The intervention integrated reflective workshops, social action mentoring, and impact evaluation to transform cognitive understanding into civic practice. The results showed a 78.5% increase in comprehensive understanding of Pancasila values and a 65.3% improvement in pro-social behavior, along with the emergence of 15 participant-initiated social action projects such as anti-hoax campaigns, interfaith dialogue forums, and mutual cooperation-based economic empowerment. These findings confirm that the integration of experiential learning with Dermayon local wisdom creates sustainable and community-driven character education. This model provides a scalable and replicable framework for strengthening civic and character education by positioning youth as active agents of socio-cultural value transformation.